Policies, Assistive Technologies, and Barriers in Inclusive Education: A Global Systematic Review (2019-2024) - Guillén-Martínez, Dennisse; Alcázar-Espinoza, Javier Alexander; Rámirez-Sánchez, Iván; Samaniego-Cobo, Teresa; Villacís-Macias, Carolina (Journal of Posthumanism, 2025)
Inclusive education aims to guarantee the universal right to equitable and quality education, addressing the structural and contextual barriers that hinder its global implementation. Although educational policies and assistive technologies have facilitated some progress, challenges persist that impede the effective inclusion of students with special educational needs (SEN). To critically analyze how educational policies, assistive technologies, and structural barriers interact in the implementation of inclusive education globally, identifying opportunities and limitations. A systematic literature review was conducted using PRISMA methodology, covering studies published between 2019 and 2024 in the Scopus database. Relevant empirical and theoretical research addresses the interrelations among policies, technologies, and structural barriers in inclusive educational contexts. The findings were grouped into three main categories.1. Assistive technologies, including agile methodologies, artificial intelligence, and educational robotics, have the potential to personalize learning and improve accessibility, albeit with ethical and practical challenges.2. Inclusive educational policies that demonstrate significant progress in some countries face issues of coherence and inequality in their implementation. 3. Structural barriers, such as limited teacher training, regional inequalities, and the coexistence of parallel educational systems, perpetuate exclusion. This study provides a comprehensive and updated view of the dynamics influencing inclusive education, highlighting the need for integrated strategies that combine assistive technologies and coherent policies. It also emphasizes the importance of an intersectoral collaborative approach for overcoming structural barriers and promoting educational equity. To advance toward an inclusive educational system, it is essential to design more equitable policies, ensure teacher training in assistive technologies, and establish regulatory frameworks that ensure ethical implementation. Additionally, fostering collaboration among governments, educational institutions, and technological actrs is recommended to address the structural barriers in diverse contexts.